Zebrafish epiboly: Spreading thin over the yolk. Issue 3 (28th October 2015) - Bruce, Ashley E.E.
Abstract : Tissue thinning and spreading, a morphogenetic movement termed epiboly, is used widely during animal development. In zebrafish, epiboly is a prominent cell movement during gastrulation, whereby a squamous epithelium (the enveloping layer), a multi‐layer of loosely packed cells (the deep cells), and a yolk nuclear syncytium (the yolk syncytial layer) undergo coordinated expansion to engulf the yolk and close the blastopore. Elucidating the mechanisms that underlie epiboly is important not only for understanding animal development in general, but also for providing insights into fundamental cell behaviors including cell intercalation, cell adhesion, cell signaling, and epithelial morphogenesis. Here, recent work is reviewed with a focus on findings that advance our understanding of (1) the role of actomyosin motors in the yolk cell to drive epiboly, (2) the mechanisms that underlie the spreading of the epithelial enveloping layer, and (3) the regulation of deep cell movements by E‐cadherin based adhesion. A discussion of how these new insights add to the current view of epiboly and future prospects is also presented. Overall, the study of zebrafish epiboly can provide general and broadly applicable insights into the genetic, molecular, and cellular control of morphogenesis. Developmental Dynamics 245:244–258, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Two different actomyosin motors in the yolk cell are important drivers of zebrafish epiboly. Orientation of cell divisions along the axis of tension facilitates spreading of the outer epithelium during epiboly. Proper trafficking of E‐cadherin is required for efficient cell movements during epiboly.